2016
DOI: 10.1016/j.radcr.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Massive gas gangrene secondary to occult colon carcinoma

Abstract: Gas gangrene is a rare but often fatal soft-tissue infection. Because it is uncommon and the classic symptom of crepitus does not appear until the infection is advanced, prompt diagnosis requires a high index of suspicion. We present a case report of a middle-aged man who presented with acute onset lower-extremity pain that was initially thought to be due to deep vein thrombosis. After undergoing workup for pulmonary embolism, he was found to have massive gas gangrene of the lower extremity secondary to an occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Over 83% (5/6) of patients who did undergo DRE demonstrated positive findings, including a palpable mass (4), purulent anal drainage (1), and pain out of proportion (1). This over 80% rate of positive findings on DRE is consistent with a study by the World Journal of Gastroenterology in 2015 which showed that preoperative DRE resulted in positive findings in 75% of FG with underlying rectal cancer and it highlights the importance of including a thorough anorectal examination in all patients with FG [1,3,[15][16][17].…”
Section: Diagnosissupporting
confidence: 65%
See 1 more Smart Citation
“…Over 83% (5/6) of patients who did undergo DRE demonstrated positive findings, including a palpable mass (4), purulent anal drainage (1), and pain out of proportion (1). This over 80% rate of positive findings on DRE is consistent with a study by the World Journal of Gastroenterology in 2015 which showed that preoperative DRE resulted in positive findings in 75% of FG with underlying rectal cancer and it highlights the importance of including a thorough anorectal examination in all patients with FG [1,3,[15][16][17].…”
Section: Diagnosissupporting
confidence: 65%
“…The antibiotic regimen should cover Staphylococcus, Enterococcus, Escherichia coli, and other Gram-negative pathogens and anaerobes (including Bacteroides and Clostridium species). Most commonly used agents include broad-spectrum penicillin with a beta-lactamase inhibitor, a second-or third-generation cephalosporin, a carbapenem, in combination with agents that cover potentially resistant Gram-positive bacteria and anaerobes, i.e., Vancomycin or Daptomycin, Clindamycin, and/or Metronidazole [5,6,14,16]. As soon as culture results are available, a targeted therapy should be implemented.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Nontraumatic gas gangrene may be associated with colon cancer [31,32]. An 81-year-old female patient with rectal cancer became acutely ill with abdominal pain and paralytic ileus.…”
Section: Nontraumatic Gas Gangrenementioning
confidence: 99%
“…septicum is the main etiological agent of spontaneous myonecrosis, even though infection can also manifest as fatal, necrotizing enterocolitis or distal ileitis [223][224][225][226][227][228][229]. It is not part of the normal human intestinal and stool flora [230,231] possibly is an opportunistic pathogen, but is part of the normal gastrointestinal microbiota of many animals [232,233].…”
Section: Septicum Toxinsmentioning
confidence: 99%
“…Diagnosis of spontaneous myonecrosis is difficult and the symptoms are result of an fast systemic infection [237]. Due to the low incidence of this infection, no preventive protocols have been developed, the most prone patients (for example immunosuppressed, with a history of gastric diseases) should undergo a preventive diagnosis, but that has not been implemented yet [227,229,238]. The work of Michael J. G. Mallozzi et al [239] show an excellent review of several aspects of the infection of C. septicum encompassing the diagnosis of the same.…”
Section: Septicum Toxinsmentioning
confidence: 99%